Successes, Challenges, and Future Directions for an Urban Full Service Community Schools Initiative. Issue 7 (September 2019) - Anderson, Jeffrey Alvin; Chen, Ming-E; Min, Mina; Watkins, Lara L.
After receiving a multiyear federal grant, an urban school district and community agency that focused on family literacy implemented a comprehensive school reform initiative called Providence Full Service Community Schools (PFSCS). A host of community partners collaborated to develop the PFSCS model with the broad goal of strategically connecting teachers, families, afterschool programming, and community services, as a method for improving the well-being of students in participating schools and their families. This article compares findings from a baseline and 4-year follow-up study of the PFSCS, documenting changes in stakeholder perceptions about the project. In the follow-up study, respondents noted increased family engagement and improved climate in PFSCS schools, along with more school–community partnerships. Findings also suggested stakeholder perceptions had changed regarding the extent to which the PFSCS was expected to improve academic achievement. Specifically, although some stakeholders were disappointed that a direct link between the PFSCS and improved test scores had not been found, findings also indicated that overall, the community continued to value the work and desired to see the program expand.